Sindrom Hipoventilasi Obesitas (Pickwickian Syndrome): Laporan Kasus - Novia, Juvita; Ida Bagus, Aditya Nugraha; Wira, Gotera (Fakultas Kedokteran, Universitas Andalas, 2025)
Background: Obesity hypoventilation syndrome (OHS) or Pickwickian syndrome is a chronic respiratory disorder characterized by the combination of obesity, daytime hypercapnia, and sleep-related breathing disturbances. This condition is often underdiagnosed and may increase the risk of morbidity and mortality. Case: A 30-year-old male presented with complaints of shortness of breath, snoring during sleep, frequent nighttime awakenings, fatigue, and headaches. The patient was severely obese and had a history of hypertension, type 2 diabetes mellitus, and a 15-year history of smoking one pack of cigarettes daily. He was diagnosed with severe community-acquired pneumonia (CAP) with sepsis, right heart failure, and OHS. The patient received ventilatory support, diuretics, antibiotics, blood glucose regulation with insulin, and physiotherapy. Discussion: During hospitalization, the patient had difficulty weaning from the ventilator due to OHS. The diagnosis was based on three main criteria: a body mass index >30 kg/m², daytime PaCO₂ >45 mmHg, and sleep-disordered breathing in the absence of other causes of alveolar hypoventilation. Conclusion: OHS should be promptly recognized and managed through a multidisciplinary approach to reduce morbidity and mortality. Education and clinical awareness of this syndrome must be improved, as it is frequently underdiagnosed. Keywords: obesity, hypoventilation, pickwickian syndrome, sleep disorder